THE IMPLEMENTATION OF SELF-ASSESSMENT IN WRITING CLASS: A CASE STUDY AT STBA LIA JAKARTA - Purwanti, Theresia Tuti (TEFLIN Journal, 2015)
Self-assessment has become a means of realizing the goals of learner-centered education. It is conducted to help students grow to be independent learners. With regard to this point, this case study is aimed at investigating the implementation of the self-assessment as a learning tool in writing class. Its purpose is to examine students' reactions to the use of self-assessment checklist and how it helps them revise their essays. To do this, the data of (1) students' essays; (2) students' self-assessment checklist; and (3) students responses to the questionnaires on their attitudes towards self-assessment practice obtained from nine students were analyzed. The findings revealed that most students welcomed the use of self-assessment. Most students found the process of reflecting on one's own learning to be helpful. After the implementation of self-assessment, the students show that they can revise the essays at phrase level, surface level, content level, and lexical level. However, their grammatical accuracy did not progress significantly.